Mechanism of the Curative Effect of Wen-Shen-Jian-Pi Prescription in the Treatment of Amyotrophic Lateral Sclerosis - Gong, Fan; Zhu, Wei; Liao, Weilong; Wang, Mingzhe; Zheng, Xuanlu; Wang, Chenghui; Liu, Te; Pan, Weidong (Frontiers in Aging Neuroscience, 2022)
Objective: To study the mechanism of the effect of Wen-Shen-Jian-Pi (WSJP) prescription on an ALS model comprising mice knocked out for an encoding RNA editing, mice (AR2). Methods: Twenty-four transgenic AR2 mice were randomly divided into a vehicle group, a low dose WSJP group (15 mg), a medium-dose WSJP group (30 mg), and a high-dose WSJP group (45 mg) (all n = 6 per group). In the treatment groups, the WSJP prescription was given once a day while the vehicle group was fed the same volume of water. The weekly changes in body weight, rotarod test, and grip strength were used to detect the changes in the AR2 and changes of the number of normal mitochondria, abnormal mitochondria, and autophagosomes in injured spinal cord cells were used to evaluate the pathogenetic effects of WSJP treatment, Results: The WSJP-treated AR2 mice gained weight more quickly from 8 weeks, and showed active behavior and displayed significantly better constant rotarod scores and grip strengths during the experiment compared with those of the vehicle AR2 mice. The number of normal mitochondria in the WSJP-treated AR2 mice had significantly more normal mitochondria than the vehicle group, while the numbers of abnormal mitochondria and autophagosomes were greatly decreased compared with those in the vehicle group. Conclusion: The WSJP prescription could delay the decline in motor function of ALS model mice by reducing the degeneration of neurons. The potential of WSJP to treat ALS should be assessed in a clinical trial.